1986
DOI: 10.1007/bf03348112
|View full text |Cite
|
Sign up to set email alerts
|

Urinary catecholamine excretion in patients with secondary adrenocortical insufficiency

Abstract: To evaluate the relationship between the secretion of cortisol and the activity of adrenal medulla in the secondary adrenocortical insufficiency, the excretion of epinephrine and norepinephrine was documented in 8 patients suffering from panhypopituitarism. Plasma levels and urinary excretion of cortisol were very low in baseline conditions, and the increase in these parameters of cortisol secretion occurring upon ACTH infusion was significantly reduced with respect to the response to ACTH documented in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The degenerative effect of prednisolone on the chromaffin cells appeared to be secondary to the adrenocortical hypofunction. This is supported by the article of Mpoy and Kolanowski (1986) who reported that in adrenocortical insufficiency, the excretion of epinephrine is reduced proportionally to the decrease in adrenocortical activity. Based on the results drawn of the present investigation, it could be say that treatment with prednisolone resulted in evidence of regression of most of the adrenal cells.…”
Section: Discussionmentioning
confidence: 59%
“…The degenerative effect of prednisolone on the chromaffin cells appeared to be secondary to the adrenocortical hypofunction. This is supported by the article of Mpoy and Kolanowski (1986) who reported that in adrenocortical insufficiency, the excretion of epinephrine is reduced proportionally to the decrease in adrenocortical activity. Based on the results drawn of the present investigation, it could be say that treatment with prednisolone resulted in evidence of regression of most of the adrenal cells.…”
Section: Discussionmentioning
confidence: 59%
“…Namely, urinary excretion of AD is reduced in patients with idiopathic or tuberculous Addison's disease The inner square shows the synthetic processes in the medulla as well as in the paraganglia and the outer square the process in the medulla. Open Access Journal [18], those with adrenalectomy [19], and those with secondary adrenal insufficiency [20]. Plasma AD levels of patients with Addison's disease was lower than those of healthy controls [21].…”
Section: Studies Of Ad Production In Patients With Aimentioning
confidence: 99%
“…Thus, the 24 h UFC is expectedly elevated in states of ACTH excess such as Cushing's disease and ectopic ACTH syndrome, where the adrenals are hypertrophic with consequent increased cortisol output. In the same vein, the 24 h UFC also serves as a surrogate measure of total daily ACTH secretion in patients with central hypocortisolism [11] since the magnitude of a decrease in 24 h UFC is proportional to the degree of adrenal atrophy, which in turn reflects the severity of ACTH deficiency. An obvious exception to this rule is primary adrenocortical insufficiency, where low 24 h UFC bears an inverse relationship with appropriately high plasma ACTH levels.…”
mentioning
confidence: 99%